El "stock" de capital en España y su distribución territorial (1964-2000) / Matilde Mas Ivars, Francisco Pérez García, Ezequiel Uriel Jiménez (directores) - Mas, MatildePérez, Francisco (1950-) Uriel, Ezequiel
Bibliografía: p. 241-243 -- Índices